2007
DOI: 10.1002/art.22828
|View full text |Cite
|
Sign up to set email alerts
|

Low salivary dehydroepiandrosterone and androgen‐regulated cysteine‐rich secretory protein 3 levels in Sjögren's syndrome

Abstract: Objective. Sjögren's syndrome (SS), an autoimmune disease of exocrine glands, typically starts at the time of adrenopause. We undertook this study to test the hypothesis that SS is characterized by an insufficient androgen effect at the target tissue level.Methods. We searched for androgen response elements (AREs) in the cysteine-rich secretory protein 3 (crisp-3) gene. Dehydroepiandrosterone (DHEA) responsiveness was experimentally studied using quantitative reverse transcriptase-polymerase chain reaction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 33 publications
(50 reference statements)
4
49
0
2
Order By: Relevance
“…CRISP-3 is up-regulated in a number of pathologies including prostate cancer (59,60), chronic pancreatitis (61), Sjögren's syndrome (62), and ectopic pregnancy (63). The present study demonstrated for the first time that natrin from the venoms of N. atra induces proinflammatory responses of ECs by inducing their adhesion molecule expression and, hence, monocytic cell adhesion.…”
Section: Discussionmentioning
confidence: 51%
“…CRISP-3 is up-regulated in a number of pathologies including prostate cancer (59,60), chronic pancreatitis (61), Sjögren's syndrome (62), and ectopic pregnancy (63). The present study demonstrated for the first time that natrin from the venoms of N. atra induces proinflammatory responses of ECs by inducing their adhesion molecule expression and, hence, monocytic cell adhesion.…”
Section: Discussionmentioning
confidence: 51%
“…Given the compelling data that CRISPs are ion channel regulators via their CRISP domains , these data raise the likely possibility that CRISPs regulate multiple aspects of mammalian physiology in the normal healthy state. Similarly, and as supported by several human EST and transcript profile experiments, the up-regulation of CRISPs in cases of disease indicate a role in pathogenesis (Tapinos et al, 2002;Liao et al, 2003;Bjartell et al, 2006;Laine et al, 2007).…”
Section: Discussionmentioning
confidence: 83%
“…Crisp3 was initially identified in the mouse salivary gland (Haendler et al, 1993) and later in the human as SGP28 (Kjeldsen et al, 1996). Subsequently, it was identified in human prostate (Kratzschmar et al, 1996) where it appears promising as a marker of prostate cancer (Kosari et al, 2002;Bjartell et al, 2006Bjartell et al, , 2007 and in the salivary glands where it appears promising as a marker for Sjögren's syndrome (Tapinos et al, 2002;Laine et al, 2007). The mechanism by which CRISP3 is involved in these pathological processes is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Secretion of CRISP-3 to saliva is also low in SS compared to healthy controls (21.1 AE 2.7 mg CRISP/15 min vs 97.6 AE 12.0 mg CRIPS/15 min, p = 0.008). It was also in this study shown that patients with SS had low salivary DHEA-S values compared to healthy controls (224 AE 33 pmol vs 419 AE 98 pmol, p = 0.005) and that DHEA increased CRISP-3 in labial salivary gland explants and also in cultured human acinar cells (p = 0.018) [13]. This strongly implies that the endocrine adrenal glandintracrine exocrine gland axis fails in SS.…”
Section: [ ( F I G _ 3 ) T D $ F I G ]mentioning
confidence: 77%